Preparation of Conjugates of Cytotoxic Lupane Triterpenes with Biotin - Soural, Miroslav; Hodon, Jiri; Dickinson, Niall J; Sidova, Veronika; Gurska, Sona; Dzubak, Petr; Hajduch, Marian; Sarek, Jan; Urban, Milan (Bioconjugate chemistry, 2015)
To better understand the mechanism of action of antitumor triterpenes, we are developing methods to identify their molecular targets. A promising method is based on combination of quantitative proteomics with SILAC and uses active compounds anchored to magnetic beads via biotin-streptavidin interaction. We developed a simple and fast solid-phase synthetic technique to connect terpenes to biotin through a linker. Betulinic acid was biotinylated from three different conjugation sites for use as a standard validation tool since many molecular targets of this triterpene are already known. Then, a set of four other cytotoxic triterpenoids was biotinylated. Biotinylated terpenes were similarly cytotoxic to their nonbiotinylated parents, which suggests that the target identification should not be influenced by linker or biotin. The developed solid-phase synthetic approach is the first attempt to use solid-phase synthesis to connect active triterpenes to biotin and is applicable as a general procedure for routine conjugation of triterpenes with other molecules of choice.
Keywords: nádorové buněčné linie; protinádorové látky; nádory; Biotin; Antineoplastic Agents; Cell Line, Tumor; Biotinylation; techniky syntézy na pevné fázi; biotinylace; Humans; Triterpenes; lidé; triterpeny; Solid-Phase Synthesis Techniques; Neoplasms; biotin